Justified at Last? Kissinger's Cyprus Legacy, 1974–1976. Issue 3 (4th May 2019) - Antonopoulos, Athanasios
ABSTRACT: This article focuses on the Cyprus talks between 1974 and 1976. It presents the beneficial role the former US secretary of state, Henry A. Kissinger, played in bringing the Greek and Turkish sides around the negotiating table and commit to the efforts for a mutually acceptable settlement following the 1974 Cyprus crisis. Kissinger acted as the honest broker between Ankara, Athens and Nicosia moderating each side's demands and communicating their respective positions when direct contacts were insufficient. All parties for different reasons welcomed his involvement and considered his presence a necessity necessary. Since the public in Greece and Cyprus remained hostile to him, the US secretary remained on the side-lines. Kissinger offered innovative solutions on controversial questions that prevented progress. Thanks to his contribution intense negotiations between the two Cypriot communities with the support of Greece and Turkey took place during the Ford administration. His intervention could not and did not suffice to overcome domestic conflicts and political considerations that prevailed over the efforts for a reconciliatory and mutually acceptable agreement. Nonetheless, he succeeded in paving the way for reducing tensions in the Eastern Mediterranean.